2004
DOI: 10.1021/je049955d
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Dependence of Surface Tension for Very Dilute Aqueous Solutions of Organic Nonelectrolytes

Abstract: Surface tensions of pure organic compounds and their dilute aqueous solutions (molar fraction typically x 2 < 0.015) at 298.15 K have been measured. The Szyszkowski equation has been used for correlation of the experimental surface tension data, and the ability of the equation to describe the concentration dependence of surface tension has been tested. When accurate values of surface tension were known, the Szyszkowski equation has been found to not be suitable for correlation, especially in the case when valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 41 publications
5
24
0
1
Order By: Relevance
“…For the methanol system, Vázquez et al’s data at 298.15 K does not provide the right activity coefficient as Livingston et al’s data at 303.15 K. For the systems of ethanol and 1-propanol, surface tension was taken from Strey et al’s paper at 298.15 K; in both systems, surface tension agrees with the values reported by Vázquez et al, but the number of experimental points is higher in Strey et al’s work. For the partially miscible aqueous system of 1-butanol, Habrdová et al reported surface tensions up to a molar fraction of 1-butanol x 2 = 0.0141 at 298.15 K.…”
Section: Results and Discussionmentioning
confidence: 99%
“…For the methanol system, Vázquez et al’s data at 298.15 K does not provide the right activity coefficient as Livingston et al’s data at 303.15 K. For the systems of ethanol and 1-propanol, surface tension was taken from Strey et al’s paper at 298.15 K; in both systems, surface tension agrees with the values reported by Vázquez et al, but the number of experimental points is higher in Strey et al’s work. For the partially miscible aqueous system of 1-butanol, Habrdová et al reported surface tensions up to a molar fraction of 1-butanol x 2 = 0.0141 at 298.15 K.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The critical mass concentrations of alcohol/water solutions with butanol, pentanol, and hexanol were 3%, 0.5% and 0.3%, respectively [43]. In general, the σ of n-butanol/water mixtures as well as other alcohol/water mixtures depend on their corresponding temperature and composition, and even at low n-butanol concentrations of 0 to 1 wt%, the σ value varies [43,44]. Figure 8 shows the capillary rise dynamics for four different concentrations of n-butanol/water mixtures with different values of σ.…”
Section: Effect Of Surface Tension Of the Fluids On Capillary Rise Dynamicsmentioning
confidence: 98%
“…This means that it does not apply to systems showing positive aneotropy [18,19] (the quantity ln(π * /x 2 ) would not be well defined since π would become negative in the concentration range where σ > σ 1 ) or positive second derivative of the function π (x 2 ) at any region [19][20][21][22] (since in that region the Volmer equation would not hold: the quantity ln(π * /x 2 ) would be an increasing function of π * and then Z 0 would take negative values). (c) In the dilute zone Eq.…”
Section: Some Remarks About the Working Equationmentioning
confidence: 99%